Enhancing Access to Knowledge: Promoting Open Educational Resources through IITs Library Website - Sangam, Anusha S; Tadasad, P G (Access: An International Journal of Nepal Library Association, 2025)
This study investigates the role of Indian Institutes of Technology (IIT) in promoting Open Educational Resources (OER) through their websites. Data were collected from the IIT library websites of twenty-three institutions to analyze the availability of OER links, the types of resources offered, and the use of tools such as Learning Management Systems (LMS) and online public access Catalogues (OPAC). The study shows that many IIT libraries share useful learning platforms, such as NPTEL, SWAYAM, and NDLI. This study also examined how the use of OER is linked to better national rankings. The results suggest that IITs should use OER and online learning tools to improve digital education.